A hybrid approach to perform test case prioritisation and reduction for software product line testing. (16th July 2021) - Kumar, Satendra; Kumar, Raj; Mittal, Mohit
Software Product Line (SPL) is a popular research area in software engineering which deals with many products generated simultaneously. There is a requirement for a tool or framework that can test all the products. SPL implies Test Case Prioritisation (TCP) and Test Case Reduction (TCR) techniques to alleviate the problem of testing. This paper proposes a hybrid approach which combines K-Means and Principal Component Analysis (PCA) approaches to perform SPL testing. The experimental results show that the hybrid approach-based order provides better results than the random, similarity, ICPL algorithm-based order using APFD metric. Our proposed approach reduces the test cases to the minimum amount and is also used to perform efficient SPL testing that not only improves the effectiveness and efficiency of fault detection but also improves the effectiveness of Test Suite Reduction (TSR).